1993
DOI: 10.1055/s-2007-1006665
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Cryopreserved Venous Allografts in Microvascular Surgery without Immunosuppression: An Experimental Study

Abstract: Excellent patency rates are currently established in the use of autogenous veins as interposition vein grafts in microsurgical practice. Allografts may be a viable alternative source of vein grafts. Recent advances in cryobiology have enabled the controlled freezing of tissues with preservation of vital cellular elements. Although several reports have shown the successful use of cryopreserved large-vessel allografts, few have addressed cryopreservation of microvessels (1 to 2 mm in diameter). In this study, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Raman et al= also reported that patency rates of femoral arteries in New Zealand white rabbits after allogeneic transplantation using the freeze-dry method was not satisfactory. Narayanan et al 26 reported satisfactory results after 21 days with cryopreserved venous grafts, though depression of vein immunogenicity may require longer follow-up since rejection a p pears 3 weeks after transplantation. Transmission electron microscopic (TEM) studies have shown that the result of preservation obviously differs from freeze-dried tissues to cryopreserved tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Raman et al= also reported that patency rates of femoral arteries in New Zealand white rabbits after allogeneic transplantation using the freeze-dry method was not satisfactory. Narayanan et al 26 reported satisfactory results after 21 days with cryopreserved venous grafts, though depression of vein immunogenicity may require longer follow-up since rejection a p pears 3 weeks after transplantation. Transmission electron microscopic (TEM) studies have shown that the result of preservation obviously differs from freeze-dried tissues to cryopreserved tissues.…”
Section: Discussionmentioning
confidence: 99%
“…12 The antigenicity of the tissue also appears to be reduced by freezing. 13 " 16 These results seem inspiring for the future establishment of a "tissue bank." However, there has been little description of the fate of endothelial cells at the vascular pedicle and in the capillary bed, the viability of which is critical to the long-term survival of composite tissue.…”
mentioning
confidence: 84%
“…28 Similarly, Hirase et al reported a 100% patency rate of replanted rat hind limbs at 3 months utilizing 1.5-cm-long arterial and venous cryopreserved allografts. 29 These success rates may be, in part, due to the relatively small length of the interposition graft, allowing for spontaneous re-endothelialization following immune-mediated rejection of the allograft.…”
Section: Cryopreserved Venous and Arterial Allograftsmentioning
confidence: 95%